Root Canal Shaping by Single-File Systems and Rotary Instruments: a Laboratory Study - Bane, Khaly; Faye, Babacar; Sarr, Mouhamed; Niang, Seydina O; Ndiaye, Diouma; Machtou, Pierre (Iranian Endodontic Journal, 2015)
Introduction: The aim of this study was to compare the shaping ability of two single-file systems and conventional rotary instruments in severely curved root canals of extracted human molars. Methods and Materials: Mesiobuccal canals of 120 mandibular molars with angles of curvature ranging between 25° and 35° and radii of curvature from 5 to 9 mm, were divided into three groups (n=40). In each group the canals were instrumented with either WaveOne (W), Reciproc(R) or ProTaper (P). The time required for canal shaping and the frequency of broken instruments were recorded. The standardized pre and post-instrumentation radiographs were taken to determine changes in working length (WL) and straightening of canal curvature. The presence of blockage or perforation was also evaluated. Data were analyzed using the one-way analysis of variance (ANOVA) and post-hoc Tukey’s test. The level of significance was set at 0.05. Results: Both single-instrument systems reduced the canal preparation time by approximately 50% (P<0.05). No incidence of broken instruments from single-file systems was reported; however, two F2 instruments in the P group were broken (P<0.05). Reduction in WL and straightening of canal curvature was observed in all three systems with the highest scores belonging to P system (P<0.05). No case of blockage or perforation was found during shaping in any group. Conclusion: Single-file systems shaped curved canals with substantial saving in time and a significant decrease in incidence of instrument separation, change in WL, and straightening of canal curvature.